EDAPHIC RELATIONSHIPS AMONG TREE SPECIES IN THE NATIONAL PARK AT MERAPOH, PAHANG, MALAYSIA - Nizam M S,; Norziana J,; Sahibin A R,; Latiff A, (Tropical Life Sciences Research, 2022)
A study was conducted in the National Park at Merapoh, Pahang in Peninsular Malaysia to examine the relationships between tree communities and its soil characteristics. Tree species inventory and soil samplings were carried out in 18 subplots of 10 m x 10 m within a 2-ha permanent plot. The measured soil variables include pH; organic matter (OM) content; available Mg, P and K; total inorganic-N; and content of clay and silt. A total of 251 trees were enumerated comprising of 150 species from 83 genera and 39 families. The most important species based on the highest importance value (IVi) was Knema furfuracea with an IVi of 3.96%. Soils of the study site were acidic and showed clay texture, while available nutrients were of low to medium concentrations. A floristic compositional pattern was observed among all surveyed subplots which were correlated to the edaphic variables as revealed by canonical correspondence analysis. Soil pH, inorganic-N and phosphorus appear to be the principal environmental determinants of tree communities in the study plots. Satu kajian telah dijalankan di Taman Negara di Merapoh, Pahang, Semenanjung Malaysia untuk meneliti perhubungan antara komuniti pokok dengan ciri-ciri tanah di kawasan kajian. Inventori spesies pokok dan pensampelan tanah telah dilakukan di 18 subplot berukuran 10 m x 10 m dalam satu plot kekal 2 ha. Variabel tanah yang diukur termasuk pH; kandungan bahan organik; Mg, P dan K tersedia; jumlah nitrogen tak organik; dan kandungan liat serta kelodak. Sejumlah 251 pokok telah dikira yang mengandungi 150 spesies daripada 83 genus dan 39 famili. Spesies paling penting berdasarkan nilai kepentingan tertinggi ialah Knema furfuracea dengan nilai kepentingan 3.96%. Tanah di kawasan kajian adalah berasid dan menunjukkan tekstur lempung, manakala nutrien tersedia adalah berkepekatan rendah kepada sederhana. Satu corak komposisi flora telah diperhatikan antara kesemua subplot yang dikaji, yang berkait dengan variabel edafik sebagaimana yang dihuraikan oleh analisis perhubungan kanonikal. Variabel pH tanah, nitrogen tak organik dan fosforus memperlihat sebagai faktor persekitaran utama bagi komuniti pokok dalam plot kajian.